Lumbar spinal atypical teratoid rhabdoid tumor. Issue 12 (December 2015) - Dhir, Aditi; Tekautz, Tanya; Recinos, Violette; Murphy, Erin; Prayson, Richard A.; Ruggieri, Paul; Wolff, Johannes
Highlights: Atypical teratoid rhabdoid tumor (AT/RT) is a pediatric tumor with a poor prognosis. Spinal AT/RT is a rare entity, with lumbar location even less frequently reported. Our patient had an intradural extramedullary mass extending downwards from the L3–4 level. The tumor cells showed no immunoreactivity to INI-1 antibody. No mutation was detected in the SMARCB1 gene on comprehensive analysis of blood. Abstract: We describe a pediatric patient with an atypical teratoid rhabdoid tumor (AT/RT) exclusively of the lumbar spine, with a different presentation from the two previously reported pediatric lumbar AT/RT. AT/RT are rare pediatric tumors of the central nervous system, with a dismal prognosis. Although there is sufficient literature on brain AT/RT, spinal AT/RT continues to be a rare entity, with a lumbar location even less frequently reported. A 30-month-old African American boy with multiple comorbidities presented with the inability to ambulate, encopresis and urinary dribbling. The MRI showed an intradural extramedullary mass extending downwards from the L3–4 level. He underwent an L3–S2 laminoplasty. The surgically resected mass was marked by sheets of cells with large nuclei and prominent nucleoli. The tumor cells stained with antibodies to synaptophysin and CAM5.2, and showed no immunoreactivity to INI-1 antibody. He was diagnosed with a World Health Organization Grade IV AT/RT. There was no mutation detected in the SMARCB1 gene on a comprehensive analysis of his blood. The boy is currently being treated according to the Medical University of Vienna AT/RT protocol, with no evidence of tumor recurrence 8 months after surgery. To our knowledge, this is the only report of a lumbar AT/RT in an African American child.